Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) in Africa: Current Considerations and Future Projections . (25th June 2022) - Idoko, Olubukola T; Usuf, Effua; Okomo, Uduak; Wonodi, Chizoba; Jambo, Kondwani; Kampmann, Beate; Madhi, Shabir; Adetifa, Ifedayo
Abstract: The burden of severe Covid-19 has been relatively low in sib-Saharan Africa compared to Europe and the Americas. However, SARS-CoV-2 sero-prevalence data has demonstrated that there has been more widespread transmission than can be deduced from reported cases. This could be attributed to under reporting due to low testing capacity or high numbers of asymptomatic SARS-CoV-2 infection in communities. Recent data indicates that prior SARS-CoV-2 exposure is protective against reinfection and that vaccination of previously SARS-CoV-2 infected individuals induces robust cross-reactive antibody responses. Considering these data, calls for a need for a re-think of the COVID-19 vaccination strategy in sub-Saharan African settings with high SARSCoV-2 population exposure but limited available vaccine doses. A potential recommendation would be to prioritize rapid and widespread vaccination of the first dose, while waiting for more vaccines to become available.